Newborn Apgar Score in Terms of Prenatal Screening Results - Metti, Elvia; Delima (POLTEKKES KEMENKES PADANG, 2023)
Pregnancy is part of the period of a woman's life. However, in pregnancy there are often unwanted complications. Complications or high risk in pregnancy estimated by 20% of pregnant women. The risk of the pregnancy developing into complications can be life- threatening. However, most complications can be prevented and managed if, the pregnant woman immediately seeks help from health workers and health workers are able to identify complications early. This study was conducted with an analytic cross sectional design at the BPM Working Area of Health Center the Kuranji Padang from July to November 2018. Research respondents were involved in total sampling, there were postpartum mothers within a span of three months after giving birth. The results of the screening were analyzed in relation to the APGAR score of newborns. The results showed that there was no significant difference in the mean of APGAR scores in the first and fifth minutes between mothers who had normal and abnormal blood pressure, weight gain, and uterine fundal height. There was a significant difference in the mean of APGAR scores in the first and fifth minutes between mothers who had normal and abnormal fetal movements and fetal heart rate. Birth status was the factor that has the greatest influence on the APGAR score of newborns. This study recommends the need for uniformity and completeness of data documentation by BPM in early detection of pregnant women and can provide integrated data to the Public Health Center so that the condition of pregnant women with high risk can be identified for further treatment.